ANGIOTENSIN II TYPE-1 RECEPTOR (AT1R) DISTRIBUTION IN BPH, HIGH GRADE PIN AND ADENOCARCINOMA OF THE PROSTATE - Septiadi, Isdianto; Sugandi, Suwandi; Noegroho, Bambang S; Tjahjodjati, Tjahjodjati; Safriadi, Ferry; Siregar, Safendra; Adriansjah, Ricky; Adi, Kuncoro; Sihombing, Aaron T; Pramod, Sawkar V; Nasution, Ramlan; Hernowo, Betthy S (Indonesian Urological Association, 2010)
Objective: The aim of the study was to detect the differences in number and the distribution of angiotensin II type-1 receptor (AT1R) in BPH, high grade PIN, and adenocarcinoma of the prostate. Material & method: A prospective study was performed in RSHS, in collaboration with the Department of Anatomical Pathology. Prostate samples were taken by TUR of the prostate, and then divided into 5 groups. They were BPH, high grade PIN, adenocarcinoma of the prostate in 3 difference grades (well, moderate, and poorly differentiated). Kidney tissue for control. Immunohistochemical staining was done to determine the angiotensin II type-1 (AT1R) receptor distribution as primary antibody used was mouse monoclonal antibody AT1 (TONI-1): sc-57036, Santa Cruz Biotechnology Inc., CA. Results: Angiotensin II type-1 receptor was found in material of BPH, high grade PIN and adenocarcinoma of the prostate. The number and distribution of the receptors were not different. Conclusion: There are no significant differences in number and distribution of angiotensin II type-1 receptor on BPH, high grade PIN, and adenocarcinoma of the prostate.